Metabolic Interaction Between Schwann Cells and Axons Under Physiological and Disease Conditions - Bouçanova, Filipa; Chrast, Roman (Frontiers in Cellular Neuroscience, 2020)
Recent research into axon-glial interactions in the nervous system has made a compelling case that glial cells have a relevant role in the metabolic support of axons, and that, in the case of myelinating cells, this role is independent of myelination itself. In this mini-review article, we summarize some of those observations and focus on Schwann cells (SC), drawing parallels between glia of the central and peripheral nervous systems (PNS), pointing out limitations in current knowledge, and discussing its potential clinical relevance. First, we introduce SC, their development and main roles, and follow with an evolutionary perspective of glial metabolic function. Then we provide evidence of the myelin-independent aspects of axonal support and their coupling to neuronal metabolism. Finally, we address the opportunity to use SC-axon metabolic interactions as therapeutic targets to treat peripheral neuropathies.